Forkhead box a2 (Foxa2) Gene differntiation of embryonic stem cells (Journal of Academic Research, 2024)
Foxa2 gene differntiaion in  neural stem cells exist in the mammalian developing and adult nervous system during the neural differentiation of the embryonic stem cells (ESCs). The potential of neural stem cells for the treatment of neurodegenerative diseases and brain injuries has substantially promoted research on neural stem cell self-renewal and differentiation.About the history of SCs, because they are important for replacement therapy diseases.Then, I will review literature, arguments that are dealing with,  how the SCs differentiate into neural cells, and how could  this process can be handled in vitro.The unique capability of these cells to form various tissues under definite signals received from the body, it makes this cell an object of extensive research.